EFECTO DE LOS PRECIOS DEL PETRÓLEO EN EL CRECIMIENTO ECONÓMICO: UN ANÁLISIS PARA ECUADOR, PERIODO 2007 - 2015 - Luna Villavicencio, Santiago Javier (2019)
This research determines the effect generated by oil price shocks on the economic growth of Ecuador during the 2007-2015 period. For this, time series data, an error correction model (VEC) and an autoregressive model of distributive lags (ARDL) are used. These models are used to know the effect of short and long term, generated by fluctuations in the price of oil in the Ecuadorian economy. With data from the World Development Indicators (WDI), Ecuador's economic growth is calculated through gross domestic product (GDP). On the other hand, oil price data is provided by the Central Bank of Ecuador (ECB); which helps to determine the effect on the economic growth of the country. The nature of this research establishes economic growth as the dependent variable and oil prices as the independent variable. The results obtained show that the percentage increases in oil prices increase the difference in economic growth, both in the short and long term. That is why during crisis and economic prosperity throughout the study period, economic growth has fluctuated in parallel with the economic contributions of oil exports. Therefore, the policies focused on the diversification of the productive matrix, the elaboration and export of products with added value would support the Ecuadorian economy when it is affected by the shocks of the price of “black gold”.